Integrated 3E impacts of photovoltaic systems: A comparative study of panels and windows - Na Zhao; Jia Zhang; Chao Ding (Case Studies in Thermal Engineering)
This paper evaluates the integrated benefits of photovoltaic (PV) building systems in terms of energy, economy, and environment, providing a scientific basis for low-carbon sustainable buildings. Using the renovation project of a hospital in Ordos, Inner Mongolia, as a case study, we simulated energy consumption and power generation of PV-integrated buildings with EnergyPlus and JEPlus. The study considers three retrofit scenarios: installing PV panels on the exterior walls and roofs; replacing external windows with PV windows; combining both PV panels and windows. The impact on building energy consumption, carbon emissions, and economic costs was examined under various window-to-wall ratios (WWR) and PV power capacities. A multi-objective optimization analysis was performed using the TOPSIS method to identify the most balanced solutions. The results indicate that optimal PV system configurations should balance energy consumption, carbon emissions, and costs. For scenario 1, a WWR of 0.4 and 100 W power yield the best performance. For scenario 2, a WWR of 0.2 with type 3 PV windows is optimal. For scenario 3, a WWR of 0.2, 300 W power, and type 1 PV windows effectively reduce energy consumption and carbon emissions while maximizing economic benefits.